The genus Pseudolycoriella Menzel & Mohrig (Diptera, Sciaridae) in New Caledonia, with the description of thirteen new species - Vilkamaa, Pekka; Hippa, Heikki; Mohrig, Werner (Zootaxa, 2012)
The following species of the genus Pseudolycoriella Menzel & Mohrig, 1998 are recognized from New Caledonia, allnewly described: Pseudolycoriella acicula sp. n., P. bisulca sp. n., P. capillosa sp. n., P. latiflagellata sp. n., P. pallidulasp. n., P. senticosa sp. n., P. simplex sp. n., P. spicata sp. n., P. tenuis sp. n., P. tribulosa sp. n., P. trispicata sp. n., P. tumidior sp. n. and P. villosa sp. n. A key to the species is given.